A dor e a delícia de ser o que é: a brasilidade e o caso do pertencimento como disciplina - Santos, Francisco Sá Barreto dos (2012)
Recurrently, the national identities are presented as, at the same time, the most sophisticated and simple social belonging tool, inclusion dispositive and mutual recognition of communities made complexed by the vertiginous population growth and national integration policies, very common on modern states. In Brazil, those ventures mix up with the effort to build the national experience as reflex, sometimes as rupture of the tight political bound between Portugal and his former colony, sometimes as a challenge to build an uniform projection of the people that the territory that represents, even nowadays, cultural practices so vast as in geographic extension or in public interest more immediately from most diverse groups universally mobilized by the “brasileiros” insignia. In this scenario, the “brasilidade” fulfilled – and contemporaneously still works as the best-made dispositivess to do so – the important overcoming of local experiences agenda by a subjective production logic which consolidates on the translation of “ser brasileiro” as the unique effectively legitimate spot for those born on Brazilian territory or inscribed on the national political community. A complex venture in order to produce equality political places on intensely unequal spots, a silent celebration of contemporary instruments of and to racial segregations, and the production of laws that regulates the state power as the effectively force to development, continuity and logic positivization that we could call “inclusão excludente”, act as the three main axis build by the “brasilidade” to produce the “ser brasileiro” as an emotional being, poorly engaged on political issues, good host and adept of the most diverse festive events and/or poorly connected to the urgent challenges of the movements for social change. Understand the dynamics of “política da tradição” around the build of the “brasilidade” as dispositive to social integration to the national community, in addition to search perspectives to new challenges that are inscribed on moments of overcome of the national experience as a radical politic act are the main effort propose by this work.